d5‐Reactions of Doubly Deprotonated γ,δ‐Unsaturated Carbonyl Derivatives with Electrophiles. A Novel Approach to the Synthesis of Tetrahydrofuran and Tetrahydropyran Derivatives - Dieter Seebach (2018)
The dienone‐dianion derivatives 1 react with all types of electrophiles tested (alkyl halide, silyl chloride, ester, ketone, aldehyde, epoxide) to give β, γ‐unsaturated carbonyl compounds of type A (see Formulae 2–6, 13, 14 and Tables 1–5). The α‐ and β‐hydroxyalkylation products obtained from 1a–1d can be converted to tetra‐hydrofuran and tetrahydropyran derivatives 7 and 16, respectively (Tables 1 and 2), those from the sulfur analogues 1e and 1f to ketene thioacetals 9 and to dienone derivatives 10 and 12. The t‐butyl and α‐hydroxy‐ketones are cleaved to give nitriles, amides, carboxylic acids and esters (Formulae 16‐25). The reagents 1 allow to synthesize products with distant functional groups in one step (cf. 1,8‐diketones 14 and Formulae 26–30); they correspond to the d5‐synthons 31–33; in Table 6, they are compared with other d5‐reagents. Copyright © 1982 Verlag GmbH & Co. KGaA, Weinheim